2019
DOI: 10.1158/0008-5472.can-18-3945
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Differences between Primary Colorectal Adenocarcinomas and Distant Metastases Reveal Metastatic Colorectal Cancer Subtypes

Abstract: Approximately 20% of colorectal cancer patients with colorectal adenocarcinomas present with metastases at the time of diagnosis, and therapies that specially target these metastases are lacking. We present a novel approach for investigating transcriptomic differences between primary colorectal adenocarcinoma and distant metastases, which may help to identify primary tumors with high risk for future dissemination and to inform the development of metastasis-targeted therapies. To effectively compare the transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 54 publications
9
58
0
2
Order By: Relevance
“…The M1 metastatic group is characterized by strong activation of inflammatory and immune response pathways (including immune evasion pathways, such as those involving PD-1/-L1 signaling) and enrichment in EMT activity. The M2 metastatic group exhibits MYC activation and cell proliferation [ 18 ]. Importantly, treatment modifies the gene expression profile of metastatic lesions: the immune phenotype of M1 metastases is lost in post-treatment metastases; treatment induces an enrichment of EMT activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M1 metastatic group is characterized by strong activation of inflammatory and immune response pathways (including immune evasion pathways, such as those involving PD-1/-L1 signaling) and enrichment in EMT activity. The M2 metastatic group exhibits MYC activation and cell proliferation [ 18 ]. Importantly, treatment modifies the gene expression profile of metastatic lesions: the immune phenotype of M1 metastases is lost in post-treatment metastases; treatment induces an enrichment of EMT activity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The M2 metastatic group exhibits MYC activation and cell proliferation [ 18 ]. Importantly, treatment modifies the gene expression profile of metastatic lesions: the immune phenotype of M1 metastases is lost in post-treatment metastases; treatment induces an enrichment of EMT activity [ 18 ]. The analysis of CMS groups in metastases showed the absence of CMS3 and the presence of CMS1 in only few cases; the majority of metastases were classified as CMS2 (37%) or CMS4 (45%); 86% of metastases were CMS4 in the M1 cluster, while 60% of metastases were CMS2 in the M2 cluster [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 It has been found that for more than 20% of patients CAD may metastasize. 4 Liver metastasis is the poorest prognostic factor of CAD, and the resection rate for colorectal liver metastasis remains at less than 25%. 5 Thus, the early diagnosis of liver metastasis is extremely important for enhancing the survival of CAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A new method for analyzing the transcriptomic differences between primary CAD and a distant metastasis was developed, and FBN2 and MMP3 were identified as CAD metastasis related genes, which may help predict a high-level risk of CAD metastasis. 4 Sayagués et al revealed the existence of several dysregulated genes including APOA1, HRG, UGT2B4, and RBP4 in CAD with liver metastasis samples in comparison to the primary tumor. 6 Qian et al identified higher expressions of THBS2, INHBB, and BGN in CRC patients with liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, investigators have carried out a series of explorations in this eld, and several prognostic gene signatures, 2,3 transcriptional signatures and noncoding RNA signatures have been published. [4][5][6] However, there is still no recognized prognostic prediction model, and further research is required.…”
Section: Introductionmentioning
confidence: 99%